Purification and Characterization of a New Lectin from Loach Skin Mucus - Peng-peng Sun; Yuan-yuan Ren; Jie Zheng; Ai-jun Hu (Journal of Chemistry)
Lectin from loach skin mucus plays an important role in pathogen defense. However, hardly can any paper relevant to the character of lectin from loach skin mucus be found in recent years. In this study, a kind of new lectin (LML), with a high hemagglutination activity of 166.23 × 103 HU/mg, was successfully isolated and purified from loach skin mucus. LML was a kind of glycoprotein with a molecular weight of 245 kDa. Also, the monosaccharide composition suggested that its carbohydrate chain was composed of rhamnose, arabinose, xylose, mannose, glucose, and galactose with a molar ratio of 2.02 : 11.66 : 2.06 : 1.00 : 14.09 : 6.00. Besides, LML depended on Ca2+ to induce hemagglutination and was strongly inhibited by D-lactose. The lectin exhibited powerful resistance to alkali and kept about 30% hemagglutination activity at pH 14.0, whereas its capacity of acid resistance was weak. The maximum hemagglutination activity of LML maintained at a temperature range from 20°C to 50°C. Moreover, the structure of LML was preliminarily studied, indicating it contained abundant glutamic acid, histidine, and serine, and its secondary structure contained α-helix (4.97%), β-sheet (27.55%), turns structure (49.78%), and unordered structure (17.70%).